ANTI PROLIFERATIVE ACTIVITY OF CALAMUS ROTANG AS A SPOTLIGHT ON EHRLICH’S ASCITES CARCINOMA TREATED PERITONEAL AS WELL AS SOLID TUMOR MODEL - Roy, Subeer; Kumari, Diksha; Chakraborty, Mainak; Haldar, Pallab Kanti (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
Objective: Methanol extract of Calamus rotang (MECR) root was appraised as a spotlight for the candidate of anticancer activity through the vehicle (Ehrlich Ascites Carcinoma) on Swiss albino mice. Methods: In vitro cytotoxicity assay has been accessed by trypan blue and MTT assay. In vivo anticancer activity was done using EAC cells (2 Ã— 106) where in each groups mice were 6. After treatment with MECR at the lower dose of 200 and higher dose of 400 mg/kg respectively for 9 d, half of the mice of each group were sacrificed and the rest were kept to check prolongation of life span. The anticancer potential of MECR was evaluated by tumor volume, viable and nonviable tumor cell count, tumor weight, hematological parameters, biochemical estimations and Furthermore, tissue antioxidant parameters. Besides, solid tumor activity was also inspected. Results: In MECR treated groups (200 and 400 mg/kg) tumor volume, packed cell volume and viable cell count was significantly lessened as compared to that of the EAC control group. Life span, most reliable criteria for anticancer study, increased quite surprisingly by 50% and 100% in a dose dependant manner while compared to EAC control group. The hematological, biochemical and liver tissue antioxidant parameter are significantly (p<0.05) restored along with solid tumor case study (solid tumor volume) towards the normal level after treatment with MECR. Conclusion: From the above study it can be inferred that the MECR has impressive anticancer activity in dose dependent way.